Country update: Thailand - RAYA, Angsurat (Institutional Knowledge at Singapore Management University, 2022)
Country updates from Thailand: - Burapha University Library - Chiang Mai University - Chulalongkorn University - Khunying Long Athakravisunthorn Learning Resources Center